Malta : 2010 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Malta. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Malta weathered the global recession relatively well. Real estate prices and collateral values experienced some correction and appear to have stabilized more recently, but excess supply likely remains in segments of the market. Continued progress with structural reforms will also be important to establish high value exports and to raise productivity and employment rates. Further pension reform will help avoid age-related public spending. Measures to enhance the education system and encourage women and older workers to participate in the labor market will be important to raise employment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet